2002
DOI: 10.1306/041101720129
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Properties of "Young" Carbonate Rocks, ODP Leg 166 and Boreholes Clino and Unda, Western Great Bahama Bank

Abstract: Acoustic properties determined from logs and discrete measurements along a borehole transect across the slope of the western Great Bahama Bank margin (ODP Leg 166) show a distinct relationship with primary sediment composition and noncarbonate content.Dominant sediment types are alternating cemented and uncompacted calciturbidites with shallow-water derived grains, and poorly to uncemented and compacted periplatform ooze of globigerinid-dominated wackestone to packstone. Comparison of the velocity-porosity var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Recent studies have shown that seismic properties of carbonate rocks are affected by many parameters such as rock fabric, pore type and shape, porosity, and pore fluid, making it difficult to attribute changes in seismic expression to any one parameter [ Anselmetti and Eberli , , ; Kenter et al ., , , ; Assefa et al ., ; Verwer et al ., ; Weger et al ., ; Brigaud et al ., ; Casteleyn et al ., , ]. These studies have mainly been focused on grain‐supported limestones that can have a high macropore space development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that seismic properties of carbonate rocks are affected by many parameters such as rock fabric, pore type and shape, porosity, and pore fluid, making it difficult to attribute changes in seismic expression to any one parameter [ Anselmetti and Eberli , , ; Kenter et al ., , , ; Assefa et al ., ; Verwer et al ., ; Weger et al ., ; Brigaud et al ., ; Casteleyn et al ., , ]. These studies have mainly been focused on grain‐supported limestones that can have a high macropore space development.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also provide petrophysical ranges of the porosity and permeability properties associated with micrite morphologies and proposed morphological classification partly related to those properties [Lambert et al, 2006;Richard et al, 2007;Volery et al, 2010;Deville de Periere et al, 2011]. Theories and relationships that describe sonic wave propagation in siliciclastic media [Wyllie et al, 1956[Wyllie et al, , 1958Gardner et al, 1974;and Raymer et al, 1980] are hard to apply in the complex systems of pure carbonates because of their textural complexity and their several diagenetic pathways [Kenter et al, 1997[Kenter et al, , 2002Eberli et al, 2003;Brigaud et al, 2010]. More precisely, the classic velocity-porosity transforms and the Gardner's empirical relation allow the prediction of P wave velocity from porosity or bulk density but fail to account for the variation in velocity at a given porosity value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular the process of early diagenetic (eogenesis) alteration of the primary sedimentary facies appears to be a crucial factor in understanding the rock-fabric properties (e.g. Kenter et al, 2002;Melim et al, 2001) and the NMR signal of some carbonates.…”
Section: Introductionmentioning
confidence: 99%
“…The regular and laterally continuous intercalation of the limestone beds, which are more resistant to weathering, and the softer interlayers, renders micritic calcareous rhythmites conspicuous in the field. In cores, a typical expression of calcareous rhythmites is the regular alternation of lighter and darker (e.g., Betzler et al 1999;Frank et al 1999), or of more and less porous layers (e.g., Westphal et al 2000;Kenter et al 2001Kenter et al , 2002.…”
Section: Limestone-marl Alternations and Other Micritic Calcareous Rhmentioning
confidence: 99%